THE PROTECTION OF THE PROCEDURAL PLAINTIFF IN THE PAYMENT OF REAL ESTATE IN EXECUTIVE ACTION UNDER THE PORTUGUESE CIVIL PROCEDURAL CODE: THE (NOT) UNDERSTANDING OF ARTICLE 751 OF THE CIVIL PROCESS CODE - Luís Manuel Pica (Revista Eletrônica de Direito Processual, 2020)
The Attachment, as a means of material seizure of assets of the executed, is guided by a set of requirements that the agent enforcer to respect in order to safeguard the debtor's legal position as well, one of which is the proportionality of the value of the and the nature of the seized property, and there must therefore be a quantitative link between the two. However, in view of the current scenario, such requirements are shown to be as had already occurred in the previous legislation, which tend to be more favourable to the interests of one of the parties and sometimes of some third parties who have some interest in the established legal-procedural relationship.